Language and Cognition in Gaelic-English Young Adult Bilingual Speakers: A Positive Effect of School Immersion Program on Attentional and Grammatical Skills - Garraffa, Maria; Obregon, Mateo; O’Rourke, Bernadette; Sorace, Antonella (Frontiers in Psychology, 2020)
The present study investigates linguistics and cognitive effects of bilingualism with a minority language acquired through school medium education. If bilingualism has an effect on cognition and language abilities, regardless of language prestige or opportunities of use, young adult Gaelic-English speakers attending Gaelic medium education (GME) could have an advantage on linguistic and cognitive tasks targeting executive functions. These will be reported, compared to monolingual speakers living in the same area. Furthermore, this study investigates whether there is a difference in Home Speakers of Gaelic (speakers who had acquired the language at home) compared to New Speakers of this language, i.e. whether an immersive context -as the one offered in medium education- compensates for not being native. A group of 23 monolingual English young adult speakers was compared with a group of 25 bilingual speakers attending a GME school since five years old. Participants were tested on comprehension of a set of sentences with incremental complexity in English, on their capacity to inhibit a distractor using the Test of Everyday attention (TEA) and on their performance in a Digit Span task. A tendency for a better performance on more complex linguistics and cognitive tasks was reported in bilinguals compared to monolinguals with a further advantage for New Speakers compared to Home Speakers. The study supports the idea that being bilingual in a minority language is as beneficial as speaking any other combination of languages. An immersive context of acquisition can be a good ground for developing advantages on both linguistics and cognitive tasks, with a further advantage for New speakers of the language.